Breastfeeding complexities and sociocultural barriers in the context of preventing perinatal transmission of HIV: A descriptive phenomenology in Northern Ghana - Adongo, Awinaba Amoah; Akuoko, Kofi Osei; Dapaah, Jonathan Mensah; Manful, Esmeranda (PloS one, 2025)
Although World Health Organization (WHO) policies aim to promote exclusive breastfeeding and replacement feeding for HIV-exposed infants, limited research explores the social and cultural barriers encountered by mothers living with HIV in rural health facilities in Ghana. This study investigates the challenges associated with exclusive breastfeeding and, where feasible, alternative replacement feeding among mothers living with HIV in rural areas, with a specific focus on how cultural beliefs influence adherence to recommended breastfeeding guidelines. This qualitative study was conducted in two rural community health facilities in Ghana, targeting mothers living with HIV who were actively seeking maternal and child health services. A purposive sampling technique was employed to ensure the inclusion of diverse experiences and perspectives, resulting in a sample of 32 respondents. Participants were selected based on their HIV status and engagement with maternal health services. Data collection involved in-depth interviews and interview guide as data collection tool designed to explore personal experiences and cultural influences on infant feeding practices. All interviews were transcribed verbatim and analysed using Colaizzi's descriptive phenomenological approach, facilitated by NVivo 12 software to ensure systematic data management and theme identification. The study identified specific sociocultural barriers that hinder the prevention of mother-to-child transmission of HIV in rural communities. Key themes included breastfeeding as a deeply rooted cultural practice, the customary use of water for infant feeding, traditional roles of mothers-in-law in infant care decisions, and food security concerns. Sub-themes further elaborated on breastfeeding as a long-standing tradition, perceived health benefits of breastfeeding, and respect for elders' advice, among others. These cultural norms and beliefs were found to significantly influence adherence to exclusive breastfeeding and, where feasible, alternative replacement feeding guidelines among mothers living with HIV. This study provides valuable insights into the sociocultural barriers affecting efforts to prevent mother-to-child transmission of HIV in Ghana rural areas. It highlights the need for culturally adaptive health policies and the development of community-based breastfeeding intervention programmes that align with traditional values while promoting safe feeding practices.